ANTIFERTILITY EFFECTS OF AQUEOUS LEAF EXTRACT OF OCIMUM SANCTUM LINN. (TULSI) ON SEMINAL PROFILE OF MICE - SHAIL PRAGYA; A. R. HEMBRAM; V. N. SINGH (The Bioscan, 2012)
Treatment of aqueous leaf extract of Ocimum sanctum causes significant decrease in sperm counts during 10 (p<0.05), 20(p<0.001) and 30 (p<0.001) days treatment than the control. Motility of spermatozoa also decline significantly in treated group after 10 (p<0.05), 20 (p<0.001) and 30 (p<0.001) days treatment than the control. Besides these pH of seminal plasma show significant decline in treated group of mice during 10 (p<0.001), 20 (p<0.001) and 30 (p<0.001) days treatment than the control. However mortality of spermatozoa increases significantly in treated group of mice during 10 (p<0.001), 20 (p<0.001) and 30 (p<0.001) days treatment than the control. Thus significant decrease in sperm counts, mortality, seminal pH as well as increase in mortality of spermatozoa alters the seminal quality which leads to infertility among treated group of mice.